Pregnancy complications in women with polycystic ovary syndrome - Palomba, Stefano; de Wilde, Marlieke A.; Falbo, Angela; Koster, Maria P.H.; La Sala, Giovanni Battista; Fauser, Bart C.J.M. (Human reproduction update, 2015)
The great majority of studies performed so far concerning women diagnosed with polycystic ovary syndrome (PCOS) have focused on diagnosis, menstrual cycle abnormalities, hirsutism and infertility. Although progress has been made in developing methods for achieving a pregnancy and reducing multiple gestations in women with PCOS, little attention has been paid to pregnancy complications and subsequent child outcomes. This review aims to summarize current knowledge regarding the clinical and pathophysiological features of pregnancy and children in women with PCOS. A literature search up to April 2015 was performed in PubMed, Medline, the Cochrane Library and Web of Science without language restriction. All articles were initially screened for title and abstract and full texts of eligible articles were subsequently selected. Systematic reviews with meta-analysis were initially included for each specific subject. Recent randomised controlled trials (RCTs), which were not included in the systematic reviews, were also included. In addition to evidence from meta-analyses or RCTs, we used non-randomized prospective, uncontrolled prospective, retrospective and experimental studies. When specific data for patients with PCOS were lacking, results from general population studies were reported. Women with PCOS exhibit a clinically significant increased risk of pregnancy complications compared with controls. Data which were not adjusted for BMI or other confounders demonstrated in PCOS a 3-4-fold increased risk of pregnancy-induced hypertension and pre-eclampsia, a 3-fold increased risk of gestational diabetes and 2-fold higher chance for premature delivery. Features characteristic of PCOS, such as hyperandrogenism, obesity, insulin resistance and metabolic abnormalities, may contribute to the increased risk of obstetric and neonatal complications. Limited available data suggest that offspring of women with PCOS have an increased risk for future metabolic and reproductive dysfunction. Underlying pathophysiological mechanisms of pregnancy complications along with its association with health of offspring remain uncertain. To date, the strategies for prevention and management of pregnancy complications in women with PCOS, and whether long-term health of these women is influenced, and to what extent, by pregnancy and/or pregnancy complications, remain to be elucidated. Women with PCOS show an increased risk of pregnancy complications. Heterogeneous aetiological factors involved in PCOS and associated co-morbidities may all be involved in compromised pregnancy and child outcomes. In women with PCOS, a possible relationship with genetic, environmental, clinical and biochemical factors involved in this complex condition, as well as with pregnancy complications and long-term health for both mother and child, remains to be established.